ANALISIS SISTEM INFORMASI AKUNTANSI PEMBELIAN BARANG ATK DALAM RANGKA PENGENDALIAN STOK GUDANG (Studi Kasus Pada Hotel Santika Bangka) - Candra, Muhairi; Medinal; Tri Setyo Mulyani, Hendarti (Jurnal Akuntansi Bisnis Dan Keuangan, 2019)
The purpose of this study was to find out, understand and analyze accounting information systems related to the purchase demand system, the debt payment system and warehouse goods demand system as well as how efficiently the warehouse stock control between the 2016 and 2018 purchases and usage in the hotel santika Bangka. This study uses descriptive, qualitative data analysis. Based on the results of the data analysis, it can be explained that the results of the calculation show that the company in internal control over inventory of goods at the Santika Bangka hotel is still said to be ineffective. This can be seen from the total table in 2016 amounting to 76%, in 2017 it was 119%, in 2018 it was 77%. It is effective if the percentage shows the range of 90% to 99% and 101% to 110%, it is said to be very effective if the percentage shows the number 100% while outside of that number internal inventory control of warehouse goods is said to be less effective.